2007
DOI: 10.1055/s-2007-970329
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis-Immunopathogenetic Concepts

Abstract: Sarcoidosis is a chronic granulomatous disorder characterized by an accumulation of activated lymphocytes, predominantly T helper cells, expressing the Th1 phenotype and macrophages at sites of disease activity. Although the cause of sarcoidosis has not been elucidated, several lines of evidence suggest that granuloma formation results from exposure to one or more antigens, eliciting a T lymphocyte response. The induction and evolution of granuloma formation results from a complex interplay between diverse cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 100 publications
(115 reference statements)
4
61
1
3
Order By: Relevance
“…30,31 Th1 immune response mediated by CD4 ϩ T-cells is activated in sarcoidosis and responsible for the initiation of granulomas formation. 7,8,19 Osteopontin is one of the most prominently expressed proteins in giant and epithelioid cells in sarcoidosis. 21 Recently it was shown that osteopontin can be cleaved by thrombin and several metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Th1 immune response mediated by CD4 ϩ T-cells is activated in sarcoidosis and responsible for the initiation of granulomas formation. 7,8,19 Osteopontin is one of the most prominently expressed proteins in giant and epithelioid cells in sarcoidosis. 21 Recently it was shown that osteopontin can be cleaved by thrombin and several metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…7 In sarcoidosis, CD4 ϩ lymphocytes are predominant and a smaller number of CD8 ϩ T-cells are typically present in the periphery of granulomas. 12,17 We observed a similar distribution of CD4 ϩ and CD8 Figure 2H).…”
Section: With Characteristic Features Of Granulomas In Human Sarcoidosismentioning
confidence: 99%
“…+ helper T-cells after exposure to an as yet elusive antigen under the regulatory influence of cytokines produced by local mononuclear phagocytes, T-cells, dendritic cells and fibroblasts [1,2]. According to the course of the disease, patients can be classified as being affected by acute or chronic sarcoidosis [3].…”
mentioning
confidence: 99%
“…Moreover, this key Th1 transcription factor, T-bet, directs Th1 lineage commitment [8]. Although sarcoidosis is a predominantly Th1 immune disease [9,10], and CXCR3 and IFN-c are implicated in its pathogenesis, there is currently no information about the involvement of the Th1 transcription factor T-bet in this disorder.…”
mentioning
confidence: 99%